Heat Exchange and Thermal Modes of Modern Ring Furnaces - V. I. Timoshpolsky; M. L. German; S. M. Kabishov; S. V. Korneev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper considers an accumulated experience concerning investigation of heat exchange and thermal modes of ring furnaces applied for heating simulation. Physical and mathematical model and methodology for theoretical investigation of round billet heating in the ring furnace are proposed in the paper.